2013
DOI: 10.1038/ejhg.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

A fast multilocus test with adaptive SNP selection for large-scale genetic-association studies

Abstract: As increasing evidence suggests that multiple correlated genetic variants could jointly influence the outcome, a multilocus test that aggregates association evidence across multiple genetic markers in a considered gene or a genomic region may be more powerful than a single-marker test for detecting susceptibility loci. We propose a multilocus test, AdaJoint, which adopts a variable selection procedure to identify a subset of genetic markers that jointly show the strongest association signal, and defines the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…We use a multi-locus adaptive joint test [15] as implemented in the R package AdaJoint [29]. The test identifies the best subset of SNPs that jointly show the strongest evidence for association with disease in a given gene through a variable selection procedure that takes into account the LD structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a multi-locus adaptive joint test [15] as implemented in the R package AdaJoint [29]. The test identifies the best subset of SNPs that jointly show the strongest evidence for association with disease in a given gene through a variable selection procedure that takes into account the LD structure.…”
Section: Methodsmentioning
confidence: 99%
“…at least three independent signals have been identified in the FGFR2 gene [11]), the standard single SNP analysis may fail to fully capture the joint effect of multiple SNPs in a given gene [12,13]. Gene-based tests provide a powerful alternative to the single SNP approach to combine the evidence of association from several genetic variants within a gene in relation to disease [14,15]. Gene-based tests have been successfully used to identify new loci in relation to height and body mass index [12], Crohn’s disease [16], and glucose and lipid levels [17] among others.…”
Section: Introductionmentioning
confidence: 99%
“…We used a multi-locus adaptive joint test 55 as implemented in the R package AdaJoint. The test identifies the best subset of SNPs that jointly show the strongest evidence for association with disease in a given gene through a variable selection procedure that takes into account the LD structure.…”
Section: Methodsmentioning
confidence: 99%
“…A noticeable limitation of previous studies is that only polymorphisms in a single candidate gene or a small subset of genes in this pathway were assessed, while some core elements of this pathway, such as LATS1/2 , were omitted . Furthermore, in addition to single‐SNP association analysis, it has been suggested that examining a group of SNPs within a biological pathway can provide complementary and valuable insights for the genetic architecture of complex diseases …”
Section: Introductionmentioning
confidence: 99%
“…1,7 Furthermore, in addition to single-SNP association analysis, it has been suggested that examining a group of SNPs within a biological pathway can provide complementary and valuable insights for the genetic architecture of complex diseases. 11,12 Considering the paucity of data on the genomic basis of disparities in breast cancer outcomes for women of African ancestry and the growing importance of Hippo pathway in breast carcinogenesis, 13 we sought to explore whether this pathway contributes to the aggressive breast cancer phenotypes observed in women of African ancestry.…”
Section: Introductionmentioning
confidence: 99%